ACE2 maybe serve as a prognostic biomarker in breast invasive carcinoma. Issue 6 (4th April 2022) - ling, Jie; Peng, Ning; luo, Lifei
Abstract: Background: Breast cancer is a frequently occurring malignant tumor in women. Angiotensin‐converting enzyme 2 (ACE2) is widely expressed in most organs; however, the association of ACE2 with prognosis and immune infiltration in breast invasive carcinoma (BRCA) remains elusive. Methods: We explored the expression level and prognostic value of ACE2 in patients with BRCA using a series of online bioinformatics analysis databases encompassing Oncomine, UALCAN, Kaplan–Meier plotter, TIMER, LinkedOmics, and GEO. qRT‐PCR was performed to verify our findings. Results: Angiotensin‐converting enzyme 2 mRNA and protein expression levels were decreased in BRCA tissues, and patients with low ACE2 expression levels had a poor prognosis. DNA promoter methylation of ACE2 significantly downregulated ACE2 expression in BRCA, while the expression of this protein was positively linked to immune infiltration of B cells, CD8 + and CD4 + T cells, neutrophils, and dendritic cells in BRCA tissues. The high expression level of ACE2 in enriched basophils, CD8 + T cells, and type‐2 helper T cells, which showed decreasing levels, indicated a better prognosis for BRCA. Enrichment analyses revealed that NF‐κB, IL‐17, and TNF signaling pathways were highly correlated to ACE2 in BRCA. Verification study revealed that downregulation of ACE2 was associated with a better prognosis in BRCA. Univariate and multivariate analysis confirmed ACE2 expression and clinical stage as independent prognostic factors for breast cancer. Conclusions: Angiotensin‐converting enzyme 2 may be a potential prognostic biomarker and target for BRCA. Nevertheless, future investigations are needed for validating our findings and promoting the clinical application of ACE2 in BRCA. Abstract : Breast cancer is a frequently occurring malignant tumor in females. Angiotensin‐converting enzyme 2 (ACE2) is widely expressed in most organs; however, the association of ACE2 with prognosis and immune infiltration in breast invasive carcinoma (BRCA) remains elusive. We explored the expression level and prognostic value of ACE2 in patients with BRCA using a series of online bioinformatics analysis databases encompassing Oncomine, UALCAN, Kaplan–Meier plotter, TIMER, LinkedOmics, and GEO. qRT‐PCR was performed to verify our findings. ACE2 mRNA and protein expression levels were decreased in BRCA tissues, and patients with low ACE2 expression levels had a poor prognosis. DNA promoter methylation of ACE2 significantly downregulated ACE2 expression in BRCA, while the expression of this protein was positively linked to immune infiltration of B cells, CD8 + and CD4 + T cells, neutrophils, and dendritic cells in BRCA tissues. The high expression level of ACE2 in enriched basophils, CD8 + T cells, and type‐2 helper T cells, which showed decreasing levels, indicated a better prognosis for BRCA. Enrichment analyses revealed that NF‐κB, IL‐17, and TNF signaling pathways were highly correlated to ACE2 in BRCA. Verification study revealed that downregulation of ACE2 was associated with a better prognosis in BRCA. Univariate and multivariate analysis confirmed ACE2 expression and clinical stage as independent prognostic factors for breast cancer. ACE2 may be a potential prognostic biomarker and target for BRCA. Nevertheless, future investigations are needed for validating our findings and promoting the clinical application of ACE2 in BRCA.